Coletivo mimese : ensino de poéticas fotográficas - Schvambach, Janaina (2017)
The present article reports on the photography production carried out in a discipline of Photography Poetics in the Contemporaneity whose main objective is to produce poetic works in photography within a Licentiate Degree in Visual Arts at the State University of Santa Catarina / Brazil. There were 15 portraits inspired by great works of art, where an experience in production united collectively teachers and students, promoting an expansion in the praxis of art